2016
DOI: 10.1007/5584_2016_132
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Social Media and Internet-Based Data in Preventing and Fighting Infectious Diseases: From Internet to Twitter

Abstract: Health threats due to infectious diseases used to be a major public health concerns around the globe till mid of twentieth century when effective public health interventions helped in eradicating a number of infectious diseases around the world. Over the past 15 years, there has been a rise in the number of emerging and reemerging infectious diseases being reported such as the Acute Respiratory Syndrome (SARS) in 2002, HINI in 2009, Middle East Respiratory Syndrome (MERS) in 2012, Ebola in 2014, and Zika in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 38 publications
1
59
0
3
Order By: Relevance
“…Online activity‐based epidemiological surveillance and forecasting is getting more and more attention. Google Trends, Twitter and other social media platform data offer an interesting tool to monitor public attention with regard to specific infectious diseases (Al‐Surimi, Khalifa, Bahkali, El‐Metwally, & Househ, ; Goff, Kullar, & Newland, ; Martin, Xu, & Yasui, ). Several studies have shown that this quantifiable attention is a good proxy for disease activity (Dugas et al, ; Klembczyk et al, ; Martin, Lee, & Yasui, ; Pollett et al, ; Strauss, Castro, Reintjes, & Torres, ; Thompson, Malik, Gumel, Strome, & Mahmud, ).…”
Section: Introductionmentioning
confidence: 99%
“…Online activity‐based epidemiological surveillance and forecasting is getting more and more attention. Google Trends, Twitter and other social media platform data offer an interesting tool to monitor public attention with regard to specific infectious diseases (Al‐Surimi, Khalifa, Bahkali, El‐Metwally, & Househ, ; Goff, Kullar, & Newland, ; Martin, Xu, & Yasui, ). Several studies have shown that this quantifiable attention is a good proxy for disease activity (Dugas et al, ; Klembczyk et al, ; Martin, Lee, & Yasui, ; Pollett et al, ; Strauss, Castro, Reintjes, & Torres, ; Thompson, Malik, Gumel, Strome, & Mahmud, ).…”
Section: Introductionmentioning
confidence: 99%
“…Using social media as a listening tool allows researchers to learn behavioral patterns, given the right search terms. Researchers have used Twitter to track influenza in the United States [18], Zika in Latin America [19], and Middle East respiratory syndrome in the Middle East [20]. These studies show that social media tracking and Internet search history can complement traditional outbreak-tracking measures.…”
Section: Social Media As a Research Toolmentioning
confidence: 99%
“…Combating public health risks has been a primary goal of healthcare systems worldwide for the better part of two centuries, as they pose significant threats to health security [1,2]. Despite extensive measures that were developed and implemented to reduce outbreaks of pandemics and epidemics, global surveillance and monitoring systems have witnessed a rise in the number of such events [1,3,4]. In recent years, the international community, led by the World Health Organization (WHO), has been called upon to manage numerous infectious disease outbreaks: the 2002 Severe Acute Respiratory Syndrome (SARS) outbreak, the 2009 H1N1 pandemic, the 2014 Ebola outbreak and the most recent 2016 Zika outbreak [1,3].…”
Section: Introductionmentioning
confidence: 99%